Utilization of the Intimacy and Sexuality Expression Preference tool in long-term care: a case study - Jones, Cindy; Moyle, Wendy; Van Haitsma, Kimberly; Hudson, Carly (Frontiers in Dementia, 2024)
Sexual wellness plays a crucial role in an individual's quality of life, interpersonal relationships, and self-concept, particularly among older adults residing in residential aged care facilities, including those with dementia. However, there is currently a limited person-centered approach to understanding the unique preferences of each older person regarding their intimate and sexual behaviors. To address this gap, the Intimacy and Sexuality Expression Preference (ISEP) tool was developed to facilitate meaningful discussions between healthcare providers professionals or workers and older individuals about their intimacy and sexuality needs and preferences. This paper explores the use of the ISEP tool with residents in long-term aged care, including those with dementia via a user-centric case study. ISEP tool interviews were conducted with 14 residents in a single residential aged care facility in Queensland, Australia. The study presented valuable insights and contextual information from using the ISEP tool, including an example of a resident's response, which provided recommendations for better supporting the resident. This involves engaging in supportive conversations to facilitate the exploration, implementation, and assessment of practical and actionable strategies to meet intimacy and sexuality needs and preferences. The ISEP tool shows promise in improving care practices and addressing the intimacy and sexuality needs of older individuals in aged care facilities. However, it is important to acknowledge that the study was conducted in a single aged care facility with a small group of residents, potentially limiting the generalisability of the findings. Further large-scale studies are necessary to establish the tool's broader applicability across different care settings.